Poslední ročník studentů sociologie po únoru 1948 - Musil, Jiří (Lidé města, 2011)
The article deals with a rarely analysed era in the history of Czech sociology, the years after the February 1948 coup d'état in Czechoslovakia. The essay describes the fates of the last-year students of sociology at the Faculty of Arts and Letters of Charles University in Prague. The author uses objective research material, as well as his own experience and documents. Objective material includes the list of courses, exam reports, lecture notes, and themes presented at seminars. Subjective material includes the author's diary entries in the years 1947-52 and his personal memories of the events, situations and actors of the Faculty of Arts and Letters at the time. The participants are represented by three students, each representing a different way of adapting to the new situation after February 1948. Another group of participants are represented by the teachers Josef Král, Jan Blahoslav Kozák, Jan Patočka and Antonín Boháč and their attitudes, behaviour towards and relations with students. Part of the essay deals with the coping methods of students studying a major, whose professors were dismissed from the faculty, emigrated or died. In a sense, it was an "abandoned" field of studies. The conclusion of the essay represents an attempt to explain the causes of the irreconcilable conflict between traditional sociology, striving for an objective description of the structure and the development of society and the then-revolutionary Marxism-Leninism. This conflict constituted the ideological framework of the students of sociology. The ideocractic conception of Marxism-Leninism explains many phenomena of the era.